Początki programu bezpośredniej dystrybucji książek w Polsce w latach 1958–1959 - Reisch, Alfred (Pamięć i Sprawiedliwość, 2012)
Because of its size, importance and openness after 1956, Poland was from the start the most signifi cant East European target country of the Free Europe Committee’s book program. Accordingly, Polish visitors to the West were the fi rst to benefi t from a new book distribution method in addition to mailings. In the fi rst three-quarters of 1957, an unprecedented number (some 55,000) persons from the satellite countries visited the West, the vast majority of whom were Poles. This provided an opportunity to deliver directly to the recipients selected litera-ture, including politically signifi cant books and periodicals, without the hindrance of postal censorship. On the other hand, only those granted exit visas to leave Poland could receive books in this fashion. At the end of that year, Free Europe Press (FEP) initiated a permanent system for the purpose of distributing by hand books of political impact to Polish intelligentsia travelling to Western Europe. Stockpiles of no more than 100 books supplied from a central stockpile in Munich were to be maintained in London and Paris, the two centers that attracted the greatest number of important visitors from Poland. Three types of literature wereenvisaged: books requested by the visitor specifi cally, books selected by two Polish FEPeditors in New York and Munich, and books published in Polish for this purpose under FEP sponsorhip. The project would operate as a branch of the mailing project through a network of Polish cultural institutions, libraries, bookshops, publishing houses, clubs and cultural associations. Among them were the Sikorski Institute in New York, the Kosciuszko Foundation, the Polish Library in London and Paris, the Polish Youth Center in Paris, and the Polish YMCA in Geneva. Their number eventually reached 30 in London and 11 in Paris and the two cities became the main publishing centers of Polish books outside Poland.The initial Polish project ran from 1958 till the summer of 1959 under the aegis of the East Europe Institute under Sam Walker and John Kirk in order to avoid any identification with the Free Eutope Committee. Through a network of distribution points in London, Paris, Rome, Stockholm, Brussels and Munich, it distributed over 1,000 books per month to East Europeans travelling in the West. After returning home, some recipients continued to request books to be sent to them by mail. This program was followed by a special book distribution project targeting the East European and Soviet delegation members attending the communist-organized 7th World Youth Festival held in Vienna from July 26 till August 4, 1959.